Identification of Long Non-Coding RNA as Potential Biomarkers for the Diagnosis of Postmenopausal Osteoporosis - Zhu Yihua; Peng Chenjian; Wang Lining; Jiang Shujun; Yang Haomiao; Zhang Kaixuan; Dai Fenglei; Ma Yong; Chu Xudong; Zhang Chunlei; Sun Haitao (International Journal of Endocrinology)
Conclusion: The lncRNA ZNF529 is significantly overexpressed in PBMC in PMOP, and bioinformatics analysis and validation experiments indicate that it is closely associated with PMOP; thus, it is expected to be a potential diagnostic marker for PMOP.